Redesigning the User-Interface: The Use of Colours in nopE-Commerce Enterprise Software - Siyanbola, Afeez Babatunde; Oluwambe, Akinmoye (SCHOLARS: Journal of Arts & Humanities, 2021)
This paper appraises the relevance of e-commerce enterprise software in contemporary business management. Enterprise packages are technological applications that automate business activities and improve efficiency in the business workflow. The study enunciated the critical role of administrating the backend of enterprise software to manage the front-end which is accessible to users. The user interface of e-commerce enterprise backend is essential in enhancing user’s performance on the software. The study explores the psychological and physiological properties of colours in redesigning the nopE-commerce enterprise software for the backend user interface to enhance the efficiency of the administrators. The objectives of the study are to download the existing the backend of nopE-commerce enterprise software, to recreate the backend of nopE-commerce enterprise software and to introduce colours into the redesigned user interface backend of nopE-commerce enterprise software. The redesigned user-interface was subjected to the evaluation of one hundred (100) selected back-end administrators working in Lagos. The responses of participants were analysed using the 5-point Likert Scale to generate mean results. The results indicated that colours stimulate actions and feelings, user interface colours in virtual environment determines the efficiency of the system and the creative interplay of orange and blue colour in e-commerce back-end user interface enhances the performance of backend managers.